Mystery shopping and coaching as a form of audit and feedback to improve community pharmacy management of non-prescription medicine requests: an intervention study. Issue 12 (14th December 2017) - Collins, Jack Charles; Schneider, Carl Richard; Naughtin, Clare Louise; Wilson, Frances; de Almeida Neto, Abilio Cesar; Moles, Rebekah Jane
Abstract : Objectives: To determine whether repeated mystery shopping visits with feedback improve pharmacy performance over nine visits and to determine what factors predict an appropriate outcome. Design: Prospective, parallel, repeated intervention, repeated measures mystery shopping (pseudopatient) design. Setting: Thirty-six community pharmacies in metropolitan Sydney, Australia in March–October 2015. Participants: Sixty-one University of Sydney pharmacy undergraduates acted as mystery shoppers. Students enrolled in their third year of Bachelor of Pharmacy in 2015 were eligible to participate. Any community pharmacy in the Sydney metropolitan region was eligible to take part and was selected through convenience sampling. Intervention: Repeated mystery shopping with immediate feedback and coaching. Outcome measures: Outcome for each given scenario (appropriate or not) and questioning scores for each interaction. Results: Five hundred and twenty-one visits were analysed, of which 54% resulted in an appropriate outcome. Questioning scores and the proportion of interactions resulting in an appropriate outcome significantly improved over time (P<0.001). Involvement of pharmacists, visit number, increased questioning score and the prescribed scenario were predictors of an appropriate outcome (P=0.008, P=0.022, P<0.001 and P<0.001, respectively). Interactions involving a pharmacist had greater scores than those without (P<0.001). Conclusions: Repeated mystery shopping visits with feedback were associated with improved pharmacy performance over time. Future work should focus on the role of non-pharmacist staff and design interventions accordingly.